Eksistensi Kitab S?ahîh? Muslim; Studi Historis Penulisan Hadits Karya Imam Muslim - Muhammad Asrori Ma'sum (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2013)
The book of S?ahîh? Muslim is consideral in the next stage after S?ahîh? Muslim. Eventthough, in some cases, it is considered in equal stage or preferred. The title of the book is realated to the name of the author, Muslim while the title initially is Jâmi’ al-S?ahîh? whwn is was writted at the beginning of the third century A.H. this article describes some aspect of the book. One of the main elements of the book is the personal and intellectual integrities of the author that secured the hadits collected. The hadits were collected in line of restricted requirement, both of transmintters and texts sides. The book is composed thoroughly and systematically. In spite of the eminent of the book, there are less confusing hadits that the qualities of texts or chain of transmitters were still debatable.